2019
DOI: 10.1093/ejcts/ezz208
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after tricuspid valve surgery concomitant with left ventricular assist device implantation in the EUROMACS registry: a propensity score matched analysis

Abstract: OBJECTIVES Tricuspid regurgitation (TR) is common in patients receiving a left ventricular assist device (LVAD). Controversy exists as to whether concomitant tricuspid valve surgery (TVS) is beneficial in currently treated patients. Therefore, our goal was to investigate the effect of TVS concomitant with a LVAD implant. METHODS The European Registry for Patients with Mechanical Circulatory Support was used to identify adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 21 publications
2
34
0
Order By: Relevance
“…The main finding was that tricuspid valve procedure in patients for whom, tricuspid repair may be considered per current ISHLT recommendation, was associated with increased mortality (10). Veen and colleagues presented data from the EUROMACS registry, showing comparable survival rates for patients with or without concomitant tricuspid valve procedure at thirty days (13% vs. 10%), in-hospital (20% vs. 17%), and one year, but diverging survival curves after two years of follow up (76% in isolated LVADs vs. 63% in patients with concomitant procedures) (7). The effect of tricuspid repair seemed to be unsustainable, resulting in comparable risks for a recurrence of moderate to severe regurgitation after one-year.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main finding was that tricuspid valve procedure in patients for whom, tricuspid repair may be considered per current ISHLT recommendation, was associated with increased mortality (10). Veen and colleagues presented data from the EUROMACS registry, showing comparable survival rates for patients with or without concomitant tricuspid valve procedure at thirty days (13% vs. 10%), in-hospital (20% vs. 17%), and one year, but diverging survival curves after two years of follow up (76% in isolated LVADs vs. 63% in patients with concomitant procedures) (7). The effect of tricuspid repair seemed to be unsustainable, resulting in comparable risks for a recurrence of moderate to severe regurgitation after one-year.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that patients in need of valve repair are their own entity of LVAD recipients. Such patients are less acute with a longer history of heart failure and fewer ischemic etiologies (7). Valvular insufficiencies, especially of the tricuspid valve, are probably-in the absence of structural defects-more an expression of secondary longterm effects of dilatation and pulmonary hypertension on the RV function in chronic heart failure rather than a symptom to treat per se.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some single-center studies showed a reduction in post-operative RHF or readmission rates in patients undergoing concomitant TVR while others could not confirm these findings (10)(11)(12)(13). In retrospective multicenter registries, TVR at the time of LVAD implantation was not associated with improved survival (4,14).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that LVAD implantation decreases pulmonary arterial pressure, central venous pressure and TR (15,16). However, about 10% of patients present with moderate-to-severe TR one year after LVAD implantation, regardless of whether they underwent TVR or not (14).…”
Section: Introductionmentioning
confidence: 99%